Epidermoid Cyst in an Unusual Location: A Case Report - Gustavo Bustamante; Alejandro Cedeño; Ligia Perez; Enmanuel Parra; Claudia Angulo (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2020)
Epidermoid cysts account for approximately 80% of follicular skin cysts. They are considered a benign condition that can occur anywhere in the body; in the microscopic examination, this cyst reveals a cavity lined by stratified squamous epithelium resembling an epidermis, a lumen filled with degenerating orthokeratin. It is sporadic in the oral cavity, representing only 1.6% of all cysts. Its appearance in the buccal mucosa has been poorly reported. The purpose of this article is to describe a case of a 22-year-old male with an epidermoid cyst in this unusual location. This entity should not be ruled out of lesions that may occur in the oral cavity, even when its incidence is extremely low.